2018
DOI: 10.1186/s40759-018-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and analytical investigation on resin impregnation behavior in continuous carbon fiber reinforced thermoplastic polyimide composites

Abstract: In molding of carbon fiber reinforced thermoplastics (CFRTP), resin impregnation behavior to fiber yarns is very important because higher viscosity of molten thermoplastics inhibites resin impregnation to the interspace among fibers. Resultant resin un-impregnation causes lower mechanical properties of CFRTP. The purpose of this study was to clarify the relation among molding method, molding conditions and resin impregnation to fiber yarns experimentally and analytically. In this study, CFRTPs using continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The final void content is already low after pre‐impregnation, but in return, the resulting product is stiff which limits its drapeability. Most of the literature describing the various thermoplastic composite preforms focuses on the impregnation behavior, and conclude about the improvement of preforms processability when using advanced semi‐finished products combining both phases 4 . However, only few articles effectively compare the processability of different preform architectures with the same matrix, and even fewer actually deal with high‐performance thermoplastic matrices 16,17 . The influence of polymer transformation from the raw pellet state to its final shape is therefore never considered, even though a transformation at the molten state is always required during the preparation of complex semi‐finished products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final void content is already low after pre‐impregnation, but in return, the resulting product is stiff which limits its drapeability. Most of the literature describing the various thermoplastic composite preforms focuses on the impregnation behavior, and conclude about the improvement of preforms processability when using advanced semi‐finished products combining both phases 4 . However, only few articles effectively compare the processability of different preform architectures with the same matrix, and even fewer actually deal with high‐performance thermoplastic matrices 16,17 . The influence of polymer transformation from the raw pellet state to its final shape is therefore never considered, even though a transformation at the molten state is always required during the preparation of complex semi‐finished products.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, only few articles effectively compare the processability of different preform architectures with the same matrix, and even fewer actually deal with high-performance thermoplastic matrices. 16,17 The influence of polymer transformation from the raw pellet state to its final shape is therefore never considered, even though a transformation at the molten state is always required during the preparation of complex semi-finished products. Modification of polymers integrity after extrusion operation has already been reported for many polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The main difference between cCFRTP composites and traditional thermoplastic composites is that the fibers of the former exist continuously in the whole material system, while the fibers of the latter are discontinuous. Therefore, the mechanical properties of cCFRTP composites are better than those of traditional discontinuous fiber reinforced composites [ 3 ], and the application prospect is wider. The continuous fiber characteristics of cCFRTP composites determine that they are highly anisotropic, so it allows various directional performance reinforcement designs.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been researched for the fabrication of CFRTPs to achieve good impregnation of the thermoplastic polymer into the carbon fiber bundles. For continuous fiber filaments, the film stacking method [21,22,26], powder impregnation method [22][23][24]26], and microblade method [25,26] have been developed. However, the high viscosity of the polymers in any of the fabrication methods often prevents impregnation, which influences the mechanical properties of the resultant CFRTPs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high viscosity of the polymers in any of the fabrication methods often prevents impregnation, which influences the mechanical properties of the resultant CFRTPs. Therefore, researchers have investigated suitable materials and molding conditions, such as pressure, temperature, and molding time, for the manufacture of high-quality CFRTPs [21][22][23][24][25][26][27][28]. Li et al [23] reported two types of PEEKs with different melt flow rates; the polymer viscosity influenced the fiber distribution and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%